Riba dan Bunga Bank dalam Hermeneutika Al-Qur’an : (Analisis Double Movement Theory) - Robiatul Adawiyah; Muhammad Iqbal Hidayat; Yusuf Hadi Wijaya; Muhammad Khozinul Afkari; Ade Naelul Huda (Al-Kauniyah: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
Riba and bank interest are complex issue that have never been fully investigated. The issue needs to be deeply studied when the definition of riba is confronted by bank interest. This study aims to describe abaut riba and bank interest on Fazrul Rahman perspective in social-historical context. He has the interpretation method that called "double movements theory. The result of the study will be describe abaut how riba and bank interest is understood as it's Quan verses are revealed on his interpretation perspectiveBeside, the low of bank interest on Fazrul Rahman perspective.